Global energy budgets and 'Trenberth diagrams' for the climates of terrestrial and gas giant planets. (3rd February 2016) - Read, P. L.; Barstow, J.; Charnay, B.; Chelvaniththilan, S.; Irwin, P. G. J.; Knight, S.; Lebonnois, S.; Lewis, S. R.; Mendonça, J.; Montabone, L.
Abstract : The climate on Earth is generally determined by the amount and distribution of incoming solar radiation, which must be balanced in equilibrium by the emission of thermal radiation from the surface and atmosphere. The precise routes by which incoming energy is transferred from the surface and within the atmosphere and back out to space, however, are important features that characterize the current climate. This has been analyzed in the past by several groups over the years, based on combinations of numerical model simulations and direct observations of the Earth's climate system. The results are often presented in schematic form to show the main routes for the transfer of energy into, out of and within the climate system. Although relatively simple in concept, such diagrams convey a great deal of information about the climate system in a compact form. Such an approach has not so far been widely adopted in any systematic way for other planets of the Solar System, let alone beyond, although quite detailed climate models of several planets are now available, constrained by many new observations and measurements. Here we present an analysis of the global transfers of energy within the climate systems of a range of planets within the Solar System, including Mars, Titan, Venus and Jupiter, as modelled by relatively comprehensive radiative transfer and (in some cases) numerical circulation models. These results are presented in schematic form for comparison with the classical global energy budget analyses for the Earth, highlighting important similarities and differences. We also take the first steps towards extending this approach to other Solar System and extrasolar planets, including Mars, Venus, Titan, Jupiter and the 'hot Jupiter' exoplanet HD 189733b, presenting a synthesis of both previously published and new calculations for all of these planets.